The Influence of Brand Image and Brand Trust on Consumers' Decisions to Purchase Aerostreet Shoes in the City of Solo - Akbarina, Farida; Dhakirah, Sanita; Putra, I Gusti Ngurah Agung Dewantara; Umar, Ahmad Ulil Albab Al; Savitri, Anava Salsa Nur (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to determine the influence of brand image and brand trust on the Purchase Decision of Aerostreet shoes among consumers in Pasuruan. This study uses a quantitative approach. Data analysis in this study used a multiple linear regression model. The sampling technique used a non-probability technique with purposive sampling type to obtain 60 samples. The research results show that brand image and brand trust have a significant effect on purchasing interest. Brand image partially influences Purchase Decision and Brand trust directly influences purchasing interest.